Treatment of a symptomatic cervical perineural cyst with ultrasound-guided cervical selective nerve root block: A case report. Issue 37 (September 2018) - Lee, Jungwon; Kim, Kilhyun; Kim, Saeyoung
Abstract: Rationale: Symptomatic cervical perineural cysts are extremely rare, and they cause radicular pain by compressing the cervical nerve root. Several methods have been applied to manage the radicular pain induced by cervical perineural cysts, including medication, percutaneous procedures, and surgery. However, these methods are associated with various outcomes and complications. The percutaneous procedure is simple and easy to perform, but if the perineural cyst wall is punctured, it can lead to secondary complications, which include aseptic meningitis and intracranial hypotension. Patient concerns: A 51-year-old woman presented with a dull pain in the left shoulder and a tingling sensation in the left dorsal arm, hand, and middle finger. Diagnosis: The patient was diagnosed with left C7 radicular pain caused by a perineural cyst. Interventions: The left C7 radicular pain did not respond to treatment with medication. Therefore, a left C7 nerve root block with local anesthetics and steroids was performed under ultrasound guidance. Adjunctively, real-time fluoroscopy with contrast was used to avoid intravascular injection. Outcome: The symptoms resolved without any complications. Lessons: In this case, perineural cyst-induced radicular pain, which was resistant to medication, was treated using ultrasound guided cervical selective nerve root block with local anesthetics and steroids. Ultrasound guidance can enable successful cervical selective nerve root block without perineural cystic wall puncture. Therefore, ultrasound-guided cervical nerve root block is an effective treatment option for radicular pain caused by a symptomatic perineural cyst.